(3GdRgOs - (3SdjeGf Hf GdCTYK Hf ESMGb Hf HTjQ GdCROj GdSLSJGfj, CHh OGhO,J (B275 (3g` s
(3ChdgG (B:s
(3MOKfG CHh OGhO GdSLSJGfi MOKfG gTGe bGd bQCJ ai cJGH HdZfi Cfg ef cdGe YjSi Hf eQje (B: (3JYedhf ddOfjG hCfJe JQRbhf ajgG HZjQ GdYed s
(3BNQgG (B:s
(3bdJ (B: (3heG ddENhGf ? bGd (B: (3GdPjf TGQ Edjge HGdCUGHY ai GdTQ ced cJGH GdRgO GdPi Cdag hUfag CHh OGhO GdSLSJGfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs